2012
DOI: 10.1088/0967-3334/33/2/243
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility ofin vivoquantification of bone-fluorine in humans by delayed neutron activation analysis: a pilot study

Abstract: Fluorine (F) plays an important role in dental health and bone formation. Many studies have shown that excess fluoride (F(-)) can result in dental or skeletal fluorosis, while other studies have indicated that a proper dosage of fluoride may have a protective effect on bone fracture incidence. Fluorine is stored almost completely in the skeleton making bone an ideal site for measurement to assess long-term exposure. This paper outlines a feasibility study of a technique to measure bone-fluorine non-invasively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 38 publications
(41 reference statements)
0
32
0
Order By: Relevance
“…We previously showed that bone fluorine content increases linearly with age (p \ 0.001) [13,18]. Fluorine was found to increase at a rate of 0.08 ± 0.01 mg F/g Ca per year.…”
Section: In Vivo Measurements: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…We previously showed that bone fluorine content increases linearly with age (p \ 0.001) [13,18]. Fluorine was found to increase at a rate of 0.08 ± 0.01 mg F/g Ca per year.…”
Section: In Vivo Measurements: Resultsmentioning
confidence: 93%
“…We employ the 19 F(n,c) 20 F reaction [13] which has a 9.6 mb cross-section. 20 F has an 11.2 s half life so irradiation of the person, transfer to a detector, and the detection of c-rays must all be performed quickly [14].…”
Section: In Vivo Measurements: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that neutron activation analysis (NAA) is a useful technique for the in vivo measurement of fluorine [12,11]. We developed a system, which measures the delayed gamma rays emitted following the decay of 20 F. This isotope is produced via the neutron capture reaction 19 F(n,c) 20 F. The system is being developed to study people who are commonly exposed to fluorine.…”
Section: Introductionmentioning
confidence: 99%
“…This work followed on from earlier studies, which showed that we could detect fluoride in the bone in the majority of adult urban Canadians in a small pilot study of volunteers. We could measure fluoride with 95% confidence in 33 out of 34 volunteers [11,12]). We employ a system, which uses the McMaster University Tandetron accelerator to irradiate both calibration phantoms and human hands.…”
Section: Introductionmentioning
confidence: 99%